Effect of endodontically treated teeth on prosthetically guided orthodontics with clear aligners: a case series - Zhang-Yu Li; Miao-Zhu Lin; Yue Wang; Xin-Ru Cai; Xiao-Dong Wang; Xue-Qing Huang (BMC, 2024)
Abstract Background Prosthetically guided orthodontics (PGO) can correct the malocclusion for better prosthetic rehabilitation in esthetic rehabilitation. Unlike conventional orthodontic treatment, only minor tooth movement is designed in PGO according to the requirement of subsequent restoration. For better appearance during the treatment, PGO is often performed with clear aligners, which have no metal brackets. It has been proven that the PGO with clear aligners can achieve generally satisfactory outcomes. However, its risk has not been fully known due to the paucity of relevant studies. Case presentation Three patients who needed esthetic rehabilitation with mild malocclusion were included in this study. After evaluation, a prosthetic solution alone was considered insufficient to provide optimal outcomes. Thus, they were treated using PGO with clear aligners (Invisalign Go, Align Technology, Santa Clara, California, USA) and accomplished prosthetic rehabilitation subsequently. Dental history and X-ray examination revealed that endodontically treated teeth (ETT) existed in all the cases. Intraoral photographs were collected to compare the pre-treatment and post-treatment dentition. After PGO, posterior ETT did not maintain their position as scheduled and lost occlusal contacts, while all the anterior teeth, including anterior ETT, were moved to the designed position. Corresponding prosthetic rehabilitation was used to solve it after consulting with the patients. Conclusions Occlusal contact loss of posterior ETT is a potential risk in PGO with clear aligners, affecting the orthodontic result.